Sustainable Shrimp Cultivation Development Strategy in Coastal Area of Tegal City, Central Java Province - Muchtar Muchtar; Mochammad Farchan; Mugi Mulyono (Airlangga University, 2020)
The current prospect of shrimp aquaculture is still making profitable business activities. However, increased production must be followed by the application of sustainable technology. The opening of new land and the management of existing land still takes into account the environmental, social and economic carrying capacity. The purpose of this study was to determine the strategy for developing sustainable shrimp culture in the coastal area of Tegal City, Central Java Province. The study was conducted from July to October 2019. This research is a descriptive study with a case study method Subdistrict Data analysis was done descriptively and SWOT analysis (Strength, weaknes, opportunity, threat). While based on the calculation of internal factors obtained a total value of 2.86 and external factors of 2.69, This value indicates that the vaname shrimp farming business in the coastal area of Tegal City is in a position to experience growth and production stability, taking into account market needs and the application of environmentally friendly cultivation technology applications.Keyword : Shrimp aquaculture, development, strategy, technology